Research care workflow in a reference clinical research center in face of Covid-19 - Cardoso, Adriana Serdotte Freitas (2021)
Objective: To develop and validate the content of care flowcharts in a Clinical Research Center during the Covid-19 pandemic.Method: development study by consensus of experts carried out from March to July/2020 in southern Brazil. The flowcharts were developed from the literature and validated by specialists considering comprehensiveness, clarity and pertinence, obtaining a 100% agreement index, on each item of the developed instruments. The study was approved by the Ethics Committee of the institution.Results: two flowcharts of care were elaborated and validated: General care to the research participant (without suspicion of Covid-19) and assistance to the research participant with suspicion or Covid-19 confirmed; which describe activities to ensure continuity of care. Conclusion: flowcharts can promote the continuity and security of research protocols. It is expected that the flows adopted can guide other institutions with a similar profile of care.